Cytoplasmic T antigens of mouse and human cells transformed by a simian virus 40 tsA mutant. - Dubbs, D R (1980)
Simian virus 40 T antigens accumulate in the cytoplasm of simian virus 40 tsA207 transformants of primary mouse kidney or human retinoblastoma cells grown at 40 degrees C in 10% serum.